Evaluation of the insertion parameters and complications of the i-gel Plus airway device for maintaining patent airway during planned procedures under general anaesthesia: a protocol for a prospective multicentre cohort study - Klementova, Olga; Bhoday, Taranpreet Kaur; Werner, Jakub; Lopez, Ana M; Donaldson, Will; Lichnovsky, Erik; Gaszyński, Tomasz; Henlin, Tomas; Bruthans, Jan; Ulrichova, Jitka; Lukes, Martin; Blaha, Jan; et al. (BMJ open, 2021)
INTRODUCTION: Supraglottic airway devices represent a less invasive method of airway management than tracheal intubation during general anaesthesia. Their continued development is focused mainly on improvements in the insertion success rate and minimalisation of perioperative and postoperative complications. The i-gel Plus is a novel, anatomically preshaped supraglottic airway device which achieves a perilaryngeal seal due to a non-inflatable cuff made of a soft thermoplastic elastomer. The purpose of this cohort study is to assess the success rate of the i-gel Plus use during elective procedures under general anaesthesia, its intraoperative performance, and the degree of postoperative complications. METHODS AND ANALYSIS: This is a multicentre, prospective, interventional cohort study. The enrolment will take place in seven centres in four European countries. We plan to enrol 2000 adult patients in total, who are scheduled for elective surgery under general anaesthesia, and with an indication for use of a supraglottic airway device for management of their airway. The study is projected to run over a period of 18 months. The primary outcome of the study is the total success rate of the i-gel Plus insertion in terms of successful ventilation and oxygenation through the device. Secondary outcomes include perioperative parameters, such as insertion time, seal/leak pressures, number of insertion attempts and postoperative adverse events and complications. Postoperative follow-up will be performed at 1 hour, 24 hours in all patients, and for selected patients at 3 and 6 months. ETHICS AND DISSEMINATION: The cohort study has received the following ethical approvals: General University Hospital Prague, University Hospital Olomouc, University Military Hospital Prague, University Hospital Barcelona, University Hospital Lodz, Antrim Area Hospital, Craigavon Area Hospital, Office for Research Ethics Committees Northern Ireland. The results will be published in peer-reviewed journals and presented at relevant anaesthesia conferences. TRIAL REGISTRATION NUMBER: ISRCTN86233693;Pre-results.
Keywords: Anesthesia, General; Humans; multicentrické studie jako téma; adult surgery; kohortové studie; celková anestezie; Airway Management; dospělí; zajištění dýchacích cest; lidé; intratracheální intubace; Cohort Studies; Intubation, Intratracheal; Adult; Laryngeal Masks; adult anaesthesia; laryngální masky; anaesthesia in urology; prospektivní studie; anaesthesia in orthopaedics; Multicenter Studies as Topic; Prospective Studies